KEMISKINAN DAN PREVALENSI STUNTING DI KABUPATEN GARUT - Bayu Kharisma; Langgeng Bangkit Utomo; Fitria Amiria Zahra; Damar Vergiyantoro; Ckris Monika Selina; Sivananda Prichantiyo; Bima Adellano; Anita; Adhitya Wardhana; Nensi Khairunnisa10 (Media Ekonomi, 2025)
To analyze the effect of poverty on the prevalence of stunting in various regions in Garut Regency, and to evaluate the effectiveness of economic empowerment programs in reducing stunting rates. This research employs a quantitative approach, specifically Logical Framework Analysis (LFA), Panel Data Analysis, Problem Tree Analysis, SWOT Analysis, and Litmus Test. The results show a positive relationship between poverty level and stunting prevalence. In addition, economic factors that contribute to reducing stunting include increased family income, improved access to health services, and supplementary feeding programs. Economic empowerment programs are effective in reducing stunting by increasing families' ability to meet children's nutritional needs.